A physically-based constitutive model and processing map of as-cast 30Cr2Ni4MoV low-pressure rotor steel. (21st August 2019) - Xu, Y; Jiao, Y X; Liu, J S; Zhao, Y
Abstract: The hot deformation behaviour of as-cast 30Cr2Ni4MoV steel was systematically investigated within a temperature range of 1173–1473 K and strain rate range of 0.001–1 s −1 using uniaxial compression tests with a Gleeble-1500D thermal simulation tester. Flow curves were obtained under these conditions and the influences of deformation parameters on their morphologies are discussed. The characteristic parameters of the flow curves were determined and expressed in the form of simple power-law Zener-Hollomon parameters. A physically-based constitutive model was developed and its predictions of flow stress agree well with experimentally-measured flow stresses. Moreover, in order to optimize the forging parameters, processing maps of as-cast 30Cr2Ni4MoV steel were established at different stains based on a dynamic material model. By analysing the processing maps and microstructure at a strain of 0.7, the optimum forging process parameters for as-cast 30Cr2Ni4MoV steel were determined to comprise temperatures ranging from 1323–1473 K and strain rates of 0.1–1 s −1 .